Students' ICT engagement mediates the relationship between family involvements and students' use of ICT for learning mathematics among Iranian secondary school students - Kaboodvand, Tahereh; Mohd Ayub, Ahmad Fauzi; Md. Yunus, Aida Suraya; Mahmud, Rosnaini (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
Information Communication Technology (ICT) has been used widely in an educational setting especially in teaching and learning mathematics. This paper examine the role of the students’ mathematics engagement in ICT as a mediator used to strengthen the relationships between family’s ICT involvement and the students' use of ICT for learning mathematics among the secondary school's students in Zanjan city Iran. The result revealed that students’ ICT engagement had the highest mean (M = 3.88±0 .48), followed by students’ use of ICT in learning Mathematics (M=3.35±0.94) and family ICT involvement (M= 3.29±0.70). Pearson correlation coefficients showed a positive relationship between family’s ICT involvement and students use of ICT in learning Mathematics (r =.335**, p = .001) and a Moderate positive relationship between students’ mathematics engagement in ICT and students use of ICT in learning Mathematics (r = .516**, p = .001). Separate mediator analyses showed that students’ mathematics engagement in ICT mediated the relationship between family ICT involvement and students’ use of ICT in learning Mathematics (β = .42, p = .000). This study finds that students were engaged with ICT when learning Mathematics and their family supports them with ICT tools, but their support does not contribute to the students' ICT engagement. Findings also indicated that the students are interested in using ICT in learning Mathematics.